The effect of nurse-led individualized education on uncertainty in illness and patient activation in patients undergoing hemodialysis: the IDEAL HD project - Seyyede Leila Sajjadi; Mansour Ghafourifard; Hamid Tayebi Khosroshahi (Renal Replacement Therapy)
Abstract Background Patients with end-stage kidney disease suffer from uncertainty in illness and low activation. Individualized education is a new approach in which education is provided on the basis of the patient’s needs and preferences. This study aims to assess the influence of nurse-led individualized education on uncertainty in illness and activation among patients undergoing hemodialysis (HD). Methods In this randomized clinical trial, a total of 102 HD patients were randomly assigned to the intervention or control groups. Patients in the intervention group (n = 51) received individualized education on the basis of their learning needs. The control group (n = 51) received routine education (the printed educational brochures). The patients’ uncertainty in illness and the patient activation were assessed before the intervention, after the intervention, and 3 months after the last session of individualized education. Data were analyzed using SPSS software (v.26). A P-value less than 0.05 was considered significant. Results The results showed that the mean scores of uncertainty in illness and activation were not significantly different between the two groups before the intervention (P = 0.56, P = 0.46). However, the mean total score of uncertainty in illness in the intervention group were lower than the control group immediately and 3 months after the intervention (P < 0.001). In addition, a significant increase in patient activation was found in the intervention group compared with control group (P < 0.001). Conclusions It is recommended to make changes in patient education strategies and utilize effective educational methods by considering each patient’s needs and preferences. Moreover, it is recommended to use individualized education at the early stage of chronic kidney disease (CKD). Trial registration Iranian Registry of Clinical Trial, IRCT20221031056352N1.